A Comparative Study of Magnetic Resonance Angiography & Digital Subtraction Angiography in Diagnosis of Cerebral Arteriovenous Malformation - Chowdhury, AH; Islam, M; Rahman, A; Chowdhury, SJH; Islam, MN; Khan, S; Rahman, KM; Mohammad, QD; Sarker, R; Mondol, G (Bangladesh Journal of Medicine, 2014)
Background and purpose: Although phase-contrast MR angiography (MRA) provides some information regarding hemodynamics of cerebral arteriovenous malformations (AVMs), but mos t Conventional MR angiographic techniques have not been helpful in this respect. We attempted to determine the value of MR digital subtraction angiography (DSA) in assessing AVM hemodynamics. Soin this retrospective observational study was carried out to compare MRA and DSA in diagnosis of cerebral AVM. Methods and materials: It was a retrospective observational study conducted in the Department of Neurology Dhaka Medical College Hospital (DMCH), Dhaka during the period of January 2010 to December 2010. Thirty patients with haemorrhagic stroke age ranging from 13 to 65 years were selected on the basis of inclusion and exclusion criteria as the study sample. MRA and DSA were done in all the selected patients. Results: The mean age of the patients of haemorrhagic stroke was 30.3±14.3years and male female ratio was 2.7:1.The venous drainage of AVM 13 and 12 were superficial and deep respectively evaluated 100% by MRA. In the diagnosis of cerebral AVM nidussize S1<3, S2:6 cm sensitivity 100% but accuracy 100% and 73.3% respectively. Sensitivity 33.3% found in diagnosis of cerebral AVM nidus size S3:>6cm, 100% sensitive in the diagnosis of superficial and deep venous drainage AVM. Regarding the eloquence of brain area 15 was no eloquence by both MRA and DSA and identification of eloquence of brain area sensitivity 73.3% and accuracy 86.7%.The feeding vessels main vessels was found 22(73.3%) in both DSA and MRA findings. Distal vessels was seen 8(26.7%) in DSA but not seen in MRA findings. Intranidal aneurysm and Angiopathic AVM were seen 3(10.0%) and 4(13.3%) respectively in DSA, Conclusion: This study was carried out to diagnose the patients presented with cerebral AVM by MRA and DSA. MRA could not be evaluated flow status of AVM, distal feeding arteries, intranidal aneurysm and angiopathic AVM which could be detected by DSA. So, DSA is superior to MRA in diagnosis of cerebral AVM. DOI: http://dx.doi.org/10.3329/bjmed.v24i2.18699 Bangladesh J Medicine 2013; 24 : 51-58